Ácidos orgânicos e probiótico na redução da colonização de Salmonella enterica Heidelberg em frangos de corte - Martins, João Carlos Gandara (2015)
In the food industry, Salmonella sp. and other pathogens represent a major threat as potential causes of foodborne diseases. The Salmonella enterica serovar Heidelberg (SH) has a great importance to public health, being currently the most frequent serotype in the official control analyzes carried out in Brazil’s Southern. In this region are concentrated the largest poultry flocks, contributing over 60 % of Brazilian production of chicken meat. To help prevent and minimize infections by pathogenic bacteria, in addition to attend the standards of biosecurity in the field and good hygiene and sanitizing programs in the industry, there is the possibility to control directly on the poultry breeding. Use of organic acids added in the diet of the fowls has an antibacterial action. In the other hand, the use of probiotics has been shown to prevent enteric diseases. This dissertation was divided into two chapters and aimed to evaluate the quantitative and qualitative reduction of SH in broiler chickens. In the first chapter the aim was to collect information on the prevalence rate of SH strain in broiler chickens. This coefficient was 100 %, being a suitable method for determining the frequency of salmonellosis in broiler chickens. In the second chapter five treatments were evaluated (a positive control and four tests), in order to reduce the colonization of SH in broilers, using organic acids and probiotic during production phase. In SH count related to the colonization of the cecum at 28 days of age differences were observed (p<0,05) among treatments. The Treatment 2 showed a count of 41 most probable number of bacterial cells per gram (MPN/g) with lower counts when compared to the positive control (5.106 MPN/g) and treatment 1 (1.354 MPN/g). The evaluation index of infected birds, there was a difference between treatments. In treatment 2, and treatment 4 reduced 58,34 % and 25 % respectively the number of fowls infected with SH. There was no effect of treatments on the performance. Administration of organic acids and probiotic used in the treatment 2 proved to be an effective tool in the SH control in broilers at 28 days of age.